India’s Hybrid Warfare Strategy towards Pakistan in the Backdrop of Social Media (2018-2022) - Fazal, Muhammad Sohail; Irfan, Adeel; Khan, Aneel Waqas (Annals of Human and Social Sciences, 2022)
Hybrid warfare with its new tool of social media has the power to change the thinking of people. This article intends to evaluate the different aspects of the Indian hybrid warfare strategy toward Pakistan through social media. Previously, Indian hybrid warfare has been discussed but social media as its tool was not discussed comprehensively. The theory of securitization provided a conceptual framework for the study and the theory served as an analytical tool in data analysis. An exploratory research approach including a qualitative method is undertaken for the study. Data were collected from both primary as well as secondary sources. The study finds out that India systematically waged hybrid warfare against Pakistan after the mid of 2018. This study makes an original contribution by pointing out India’s hybrid warfare strategy through social media’s disinformation campaigns.